A BESTA DE SETE CABEÇAS: MONSTRUOSIDADE E CONSTRUÇÃO DE FRONTEIRAS DA CULTURA - Dorneles, Vanderlei (2020)
This thesis undertakes an analysis of the apocalyptic metaphor of the seven-headed beast in its intertextuality and in its semantic system in ancient Mediterranean cultural texts. The study starts from the Apocalypse of John and the texts of the biblical world and moves forward to discover the broad textual network of this metaphor in ancient culture. The seven-headed beast metaphor is considered to be a text of culture and a system of representation of otherness. The study is based on the concepts of semiosphere, text of culture and intertextuality, as understood by theorists of the so-called Semiotics of Culture, of Russian origin, among which Lotman stands out as its main articulator. It is also based on the concept of metaphor, in line with Lakoff and Johnson; and in the notion of the monstrous as a system of representation of grotesque otherness, according to Kristeva and Cohen, among other theorists of the notion of the abject and monstrous. It starts from the assumption that common semiotic and conceptual elements, active in the memory and imagery of cultures, show the intersection of texts from different times and places. The metaphor of the beast is analyzed in its semiotic connections with ancient texts in which there is also the construction of monstrous figures with multiple heads, as in the Narmer Palette of about 3100 BC and the Tell Asmar Cylinder of 2200 BC, among others. These connections indicate that the prophetic text of the Apocalypse of John is not given in isolation from the languages ​​and culture of his time. They also allow us to see the prophetic narratives of the Apocalypse as a text of culture, capable of dialogue and production of meanings with a network of other narratives and traditions. In the light of the Semiotics of Culture, the metaphor of the beast is analyzed as a system of representation of opposing otherness, from monstrous and abject elements. Along these lines, metaphor presents itself as a tool capable of constructing defining boundaries for oneself and for others, characterizing primitive Christianity as an emerging culture distinct from the others around it, although in constant dialogue and intertwining with them